Nature-based agricultural practices in the Mediterranean agroecosystems: A meta-analysis of their benefits on crop productivity, soil quality, and biodiversity - Wilfredo Jr. Barrera; Giulia Galli; Simone Orlandini; Leonardo Verdi; Anna Dalla Marta (European Journal of Agronomy, 2026)

Insights into the structure of grey reef shark aggregation, Carcharhinus amblyrhynchos ( B leeker, 1856), in two distinct channels of the M aldivian archipelago, I ndian O cean - Andrea Parmegiani; Jacopo Gobbato; Rilwan Yoosuf; Davide Seveso; Paolo Galli; Andrew Darren Whitehead; Yameen Ismail; Simone Montano (Journal of Fish Biology, 2026)
The grey reef shark Carcharhinus amblyrhynchos is one of the most frequently encountered reef‐associated shark species in the Maldives, yet very little is known about its local size structure or population dynamics. This study provides new insights into two aggregations of C. amblyrhynchos in the Maldives, based on biometric measurements obtained with laser photogrammetry, standardized visual surveys, opportunistic behavioural observations, and video analyses of citizen science data spanning 2013–2024. In particular, between 2022 and 2023, biometric data and visual observations from two distinct sites, Villingili Kandu in North Huvadhu Atoll and Miyaru Kandu in Vaavu Atoll, were collected to preliminarily characterize the composition of these aggregations and to provide information on the ecology of grey reef sharks. The results revealed a pronounced female‐biased sex composition and occurrences of mating in both channels, as well as a potential nursery area in Miyaru Kandu. Combining these data with predation and cleaning events recorded, we suggest that these channels might constitute important key habitats for grey reef shark aggregations. Laser photogrammetry data from 353 individuals were analysed, and a robust relationship between pre‐caudal length and total length ( R 2 = 0.97) was established, enabling the derivation of a correction index through linear regression to predict and enhance the accuracy of size estimates. Finally, long‐term video records demonstrate that Villingili Kandu currently hosts the largest documented aggregation of C. amblyrhynchos in the Maldives. These initial findings provide a baseline for further studies on the drivers influencing the aggregations of this species and its life history within the archipelago.

Wildfire ash undermines the physiology of the Mediterranean coral Cladocora caespitosa - Enrico Montalbetti; Davide Seveso; Simone Farina; Simone Bava; Elisa Carta; Laura Castellano; Paolo Galli; Valerio Isa; Yohan Didier Louis; Rossana Marzaioli; Davide Moccia; Stefania Papa; et al. (Marine Environmental Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Paleoseismic evidence for the Mw∼7 1857 earthquake along the Caggiano fault system (southern Italian Apennines) - Paolo Galli; Simone Bello; Francesco Brozzetti; Antonio Galderisi; Giuseppe Naso; Antonio Pignalosa; Gianluca Benedetti; Massimo Comedini; Edoardo Peronace (Quaternary Science Reviews, 2025)

The effect of marine litter on fishery economic performance - Alice Sbrana; Simone Galli; Tommaso Russo (Fisheries Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

To change or not to change: Macrozoobenthic community variation versus persistence in Tortolì lagoon (Sardinia, Italy) - Jacopo Giampaoletti; Simone Galli; Maria Flavia Gravina; Paolo Magni; Alice Sbrana (Estuarine, Coastal and Shelf Science, 2025)

Ethical assessment of genome resource banking (GRB) in wildlife conservation - Pierfrancesco Biasetti; Elena Mercugliano; Lisa Schrade; Maria Michela Spiriti; Frank Göritz; Susanne Holtze; Steven Seet; Cesare Galli; Jan Stejskal; Silvia Colleoni; Daniel Čižmár; Raffaella Simone; et al. (Cryobiology, 2024)

Pathology of tissue loss in three key gorgonian species in the Mediterranean Sea - Jacopo Gobbato; Thierry M. Work; Martina P. Facchinelli; Federica M. Siena; Enrico Montalbetti; Davide Seveso; Yohan D. Louis; Paolo Galli; Simone Montano (Journal of Invertebrate Pathology, 2024)

Towards sustainable hydrogen production: Integrating electrified and convective steam reformer with carbon capture and storage - Diego Maporti; Simone Guffanti; Federico Galli; Paolo Mocellin; Gianluca Pauletto (Chemical Engineering Journal, 2024)

Timing and origin of the post-collisional Venda Nova and Várzea Alegre Plutons from the Araçuaí belt, Espírito Santo, Brazil - Clara Talca Onken; Jessica Eberhard-Schmid; Livia Hauser; Simone Marioni; Andrea Galli; Valdecir de Assis Janasi; Max W. Schmidt (Lithos, 2024)

Effectiveness of modified atmosphere and vacuum packaging in preserving the volatilome of Stelvio PDO cheese over time - Bruno Domingues Galli; Elisabetta Trossolo; Ilaria Carafa; Simone Squara; Andrea Caratti; Pasquale Filannino; Chiara Cordero; Marco Gobbetti; Raffaella Di Cagno (Food Chemistry, 2024)

Application of non-lethal bioSPME-LC-MS/MS for the detection of human pharmaceuticals in soft corals: A survey at the North Nilandhe atoll (Maldives) - Alessandro Becchi; Marco Mantovani; Marina Lasagni; Elena Collina; Simone Montano; Paolo Galli; Francesco Saliu (Chemosphere, 2024)

Environmental DNA metabarcoding reveals the effects of seafloor litter and trawling on marine biodiversity - Alice Sbrana; Giulia Maiello; Maria Flavia Gravina; Davide Cicala; Simone Galli; Matteo Stefani; Tommaso Russo (Marine Environmental Research, 2024)

New evidence of grey reef sharks (Carcharhinus amblyrhynchos) displaying chafing behaviors on whale shark (Rhincodon typus) individuals in the Maldives - Jacopo Gobbato; Andrea Parmegiani; Davide Seveso; Paolo Galli; Simone Montano (Marine Biodiversity, 2024)

Phthalate levels in common sea anemone Actinia equina and Anemonia viridis: A proxy of short-term microplastic interaction? - Sara Vencato; Simone Montano; Francesco Saliu; Stefania Coppa; Alessandro Becchi; Immacolata Liotta; Tommaso Valente; Mariacristina Cocca; Marco Matiddi; Andrea Camedda; Giorgio Massaro; Davide Seveso; et al. (Marine Pollution Bulletin, 2024)

Physical and cellular impact of environmentally relevant microplastic exposure on thermally challenged Pocillopora damicornis (Cnidaria, Scleractinia) - Valerio Isa; Davide Seveso; Luca Diamante; Enrico Montalbetti; Simone Montano; Jacopo Gobbato; Silvia Lavorano; Paolo Galli; Yohan Didier Louis (Science of The Total Environment, 2024)

Greenness and neuropsychiatric symptoms in dementia - Manuela Tondelli; Annalisa Chiari; Giulia Vinceti; Chiara Galli; Simone Salemme; Tommaso Filippini; Chiara Carbone; Claudia Minafra; Claudia De Luca; Riccardo Prandi; Simona Tondelli; Giovanna Zamboni (Environmental Research, 2024)

The ethical assessment of Assisted Reproductive Technologies (ART) in wildlife conservation - Barbara de Mori; Elena Mercugliano; Pierfrancesco Biasetti; Ilaria Pollastri; Maria Michela Spiriti; Daniela Florio; Francesco Andreucci; Frank Göritz; Susanne Holtze; Cesare Galli; Jan Stejskal; Silvia Colleoni; et al. (Biological Conservation, 2024)

First record of the bull shark Carcharhinus leucas (Valenciennes, 1839) from the Maldivian archipelago, central Indian Ocean - Andrea Parmegiani; Jacopo Gobbato; Davide Seveso; Paolo Galli; Simone Montano (Journal of Fish Biology, 2023)
Verified records of the bull shark Carcharhinus leucas are lacking in the Maldives. This study provides the first confirmed evidence of 23 sightings observed from 2013 to 2023 in the central and southern atolls of this archipelago. Most of the sightings occurred in close proximity to inhabited areas, where food waste is often discarded into the water, or in several dive sites, suggesting the presence of this species in different locations around central and southern atolls. Although further research is required to fully investigate the C. leucas population in the Maldives, this report documents and confirms its presence in this region.

Mucilage-induced necrosis reveals cellular oxidative stress in the Mediterranean gorgonian Paramuricea clavata - Enrico Montalbetti; Sofia Cavallo; Annalisa Azzola; Simone Montano; Paolo Galli; Monica Montefalcone; Davide Seveso (Journal of Experimental Marine Biology and Ecology, 2023)

Short-term microplastic exposure triggers cellular damage through oxidative stress in the soft coral Coelogorgia palmosa - Enrico Montalbetti; Valerio Isa; Sara Vencato; Yohan Louis; Simone Montano; Silvia Lavorano; Davide Maggioni; Paolo Galli; Davide Seveso (Marine Biology Research, 2022)

Evolution and biogeography of the Zanclea-Scleractinia symbiosis - Davide Maggioni; Roberto Arrigoni; Davide Seveso; Paolo Galli; Michael L. Berumen; Vianney Denis; Bert W. Hoeksema; Danwei Huang; Federica Manca; Daniela Pica; Stefania Puce; James D. Reimer; et al. (Coral Reefs, 2022)
Scleractinian corals provide habitats for a broad variety of cryptofauna, which in turn may contribute to the overall functioning of coral symbiomes. Among these invertebrates, hydrozoans belonging to the genus Zanclea represent an increasingly known and ecologically important group of coral symbionts. In this study, we analysed 321 Zanclea colonies associated with 31 coral genera collected from 11 localities across the Indo-Pacific and Caribbean regions, and used a multi-disciplinary approach to shed light on the evolution and biogeography of the group. Overall, we found high genetic diversity of hydrozoans that spans nine clades corresponding to cryptic or pseudo-cryptic species. All but two clades are associated with one or two coral genera belonging to the Complex clade, whereas the remaining ones are generalists associated with both Complex and Robust corals. Despite the observed specificity patterns, no congruence between Zanclea and coral phylogenies was observed, suggesting a lack of coevolutionary events. Most Zanclea clades have a wide distribution across the Indo-Pacific, including a generalist group extending also into the Caribbean, while two host-specific clades are possibly found exclusively in the Red Sea, confirming the importance of this peripheral region as an endemicity hotspot. Ancestral state reconstruction suggests that the most recent common ancestor of all extant coral-associated Zanclea was a specialist species with a perisarc, occurring in what is now known as the Indo-Pacific. Ultimately, a mixture of geography- and host-related diversification processes is likely responsible for the observed enigmatic phylogenetic structure of coral-associated Zanclea .

Reef complexity influences distribution and habitat choice of the corallivorous seastar Culcita schmideliana in the Maldives - Enrico Montalbetti; Luca Fallati; Marco Casartelli; Davide Maggioni; Simone Montano; Paolo Galli; Davide Seveso (Coral Reefs, 2022)
The cushion seastar Culcita schmideliana has gained major attention in the last few years because of its selective predation on juvenile corals, as well as its ability to generate large demographic assemblages, causing delays in coral recovery after large mortality events in the Republic of Maldives. However, a lack of data regarding the factors affecting its distribution and habitat selection still persists in this area. Here, we adopted a novel approach in the study of corallivorous seastar habitat selection that combined ecological and digital photogrammetry data. In this regard, we tested 3 different parameters as factors influencing seastar habitat choice in the South-East region of Faafu Atoll, Republic of Maldives, namely prey abundance, Linear Rugosity Index (LRI), and Average Slope (AS). The analysis of selectivity coefficient (Ei) of seastars for different habitat types showed a preference for reefs characterized by medium AS values (Ei = 0.268), a LRI included between 2 and 2.5 (Ei = 0.180), and a juvenile coral density ranging between 10 and 20 colonies m −2 (Ei = 0.154). A multiple linear regression analysis showed that different AS and LRI values explained the 43.1% ( R 2 = 0.431, P = 0.007) and the 48.1% ( R 2 = 0.481, P = 0.024) of variance in seastars abundance, respectively, while juvenile coral densities did not significantly affect this ( R 2 = 0.132, P = 0.202). These results provide new information on the distribution and behaviour of an important corallivore of Maldivian reefs, such as C. schmideliana .

Development of ELISA Using Recombinant Proteins for the Diagnosis of Mycoplasma hyopneumoniae Infection - Simone Simionatto; Silvana Beutinger Marchioro; Marcelo dos Santos Barbosa; Vanessa Galli; Clarice Brink Brum; Sergio Jorge; Odir Antonio Dellagostin (Indian Journal of Microbiology, 2022)

Morpho-molecular traits of Indo-Pacific and Caribbean Halofolliculina ciliate infections - Simone Montano; Davide Maggioni; Giulia Liguori; Roberto Arrigoni; Michael L. Berumen; Davide Seveso; Paolo Galli; Bert W. Hoeksema (Coral Reefs, 2020)

A mesophotic hotel: the octocoral Bebryce cf. grandicalyx as a host - Davide Maggioni; Simone Montano; Oliver Voigt; Davide Seveso; Paolo Galli (Ecology, 2020)

Investigating the heat shock protein response involved in coral bleaching across scleractinian species in the central Red Sea - Davide Seveso; Roberto Arrigoni; Simone Montano; Davide Maggioni; Ivan Orlandi; Michael L. Berumen; Paolo Galli; Marina Vai (Coral Reefs, 2020)

Symbiont footprints highlight the diversity of scleractinian‐associated Zanclea hydrozoans (Cnidaria, Hydrozoa) - Federica Manca; Stefania Puce; Annalisa Caragnano; Davide Maggioni; Daniela Pica; Davide Seveso; Paolo Galli; Simone Montano (Zoologica Scripta, 2019)
Hydrozoans of the genus Zanclea have been acknowledged only recently as a fundamental component of the highly diverse fauna associated with reef‐building scleractinian corals. Although widely distributed in coral reefs and demonstrated to be important in protecting corals from predation and diseases, the biodiversity of these hydrozoans remains enigmatic due to the paucity of available morphological characters, incomplete morphological characterisations and the possible existence of cryptic species. Recently, molecular techniques have revealed the existence of multiple hidden genetic lineages not yet supported by diagnostic morphological characters. In this work, we further explore the morpho‐diversity of three genetic lineages, namely Zanclea associated with the coral genera Goniastrea (clade I), Porites (clade II) and Pavona (clade VI). Aside from providing a complete classical characterisation of the polyp and medusa stage of each clade, we searched for new potential taxonomic indicators either on symbiotic hydroids or on host corals. On the hydroids, statistical analyses on almost 7,000 nematocyst capsules revealed a significant difference in terms of nematocyst size among the three Zanclea clades investigated. On each host coral genus, we identified peculiar skeletal modifications related to the presence of Zanclea symbionts. Lastly, we discussed the potential diagnostic value of these footprints in the characterisation of Zanclea –scleractinian associations.

New insights into the ecology and corallivory of Culcita sp. (Echinodermata: Asteroidea) in the Republic of Maldives - Enrico Montalbetti; Luca Saponari; Simone Montano; Davide Maggioni; Inga Dehnert; Paolo Galli; Davide Seveso (Hydrobiologia, 2019)

Diel modulation of Hsp70 and Hsp60 in corals living in a shallow reef - Davide Seveso; Simone Montano; Davide Maggioni; Francesca Pedretti; Ivan Orlandi; Paolo Galli; Marina Vai (Coral Reefs, 2018)

Monitoring and assessing a 2-year outbreak of the corallivorous seastar Acanthaster planci in Ari Atoll, Republic of Maldives - Luca Saponari; Enrico Montalbetti; Paolo Galli; Giovanni Strona; Davide Seveso; Inga Dehnert; Simone Montano (Environmental Monitoring and Assessment, 2018)

Using a multi-method approach based on soil radon deficit, resistivity, and induced polarization measurements to monitor non-aqueous phase liquid contamination in two study areas in Italy and India - Mauro Castelluccio; Sudha Agrahari; Gabriele De Simone; Francesca Pompilj; Carlo Lucchetti; Debashish Sengupta; Gianfranco Galli; Pierluigi Friello; Pierpaolo Curatolo; Riccardo Giorgi; Paola Tuccimei (Environmental Science and Pollution Research, 2018)

Genetic diversity of the Acropora-associated hydrozoans: new insight from the Red Sea - Davide Maggioni; Simone Montano; Roberto Arrigoni; Paolo Galli; Stefania Puce; Daniela Pica; Michael L. Berumen (Marine Biodiversity, 2017)

Description of Turritopsoides marhei sp. nov. (Hydrozoa, Anthoathecata) from the Maldives and its phylogenetic position - Davide Maggioni; Stefania Puce; Paolo Galli; Davide Seveso; Simone Montano (Marine Biology Research, 2017)

Land use and land cover (LULC) of the Republic of the Maldives: first national map and LULC change analysis using remote-sensing data - Luca Fallati; Alessandra Savini; Simone Sterlacchini; Paolo Galli (Environmental Monitoring and Assessment, 2017)

Habitat preferences of the Pteroclava krempfi-alcyonaceans symbiosis: inner vs outer coral reefs - Simone Montano; Virginia Allevi; Davide Seveso; Davide Maggioni; Paolo Galli (Symbiosis, 2017)

Cerebrospinal fluid anti-Epstein-Barr virus specific oligoclonal IgM and IgG bands in patients with clinically isolated and Guillain-Barré syndrome - Diana Ferraro; Veronica Galli; Anna Maria Simone; Roberta Bedin; Francesca Vitetta; Elisa Merelli; Paolo Frigio Nichelli; Patrizia Sola (Journal of NeuroVirology, 2017)

A cryptic species in the Pteroclava krempfi species complex (Hydrozoa, Cladocorynidae) revealed in the Caribbean - Simone Montano; Davide Maggioni; Paolo Galli; Bert W. Hoeksema (Marine Biodiversity, 2017)

First record from the Atlantic: a Zanclea-scleractinian association at St. Eustatius, Dutch Caribbean - Simone Montano; Paolo Galli; Bert W. Hoeksema (Marine Biodiversity, 2017)

Molecular evidence for cryptic species in Pteroclava krempfi (Hydrozoa, Cladocorynidae) living in association with alcyonaceans - Davide Maggioni; Simone Montano; Davide Seveso; Paolo Galli (Systematics and Biodiversity, 2016)

Spatial variability in distribution and prevalence of skeletal eroding band and brown band disease in Faafu Atoll, Maldives - Simone Montano; Aurora Giorgi; Matteo Monti; Davide Seveso; Paolo Galli (Biodiversity and Conservation, 2016)

Entoprocta–sponge associations in the Indian Ocean - Aurora Giorgi; Matteo Monti; Paolo Galli; Simone Montano (Coral Reefs, 2016)

Pteroclava krempfi-octocoral symbiosis: new information from the Indian Ocean and the Red Sea - Davide Seveso; Simone Montano; Daniela Pica; Davide Maggioni; Paolo Galli; Virginia Allevi; Azzurra Bastari; Stefania Puce (Marine Biodiversity, 2016)

Slow progression of black band disease in Goniopora cf. columna colonies may promote its persistence in a coral community - Simone Montano; Giovanni Strona; Davide Seveso; Davide Maggioni; Paolo Galli (Marine Biodiversity, 2015)

The occurrence of an Acanthaster planci outbreak in Ari Atoll, Maldives - Luca Saponari; Simone Montano; Davide Seveso; Paolo Galli (Marine Biodiversity, 2015)

Mushroom corals as newly recorded hosts of the hydrozoan symbiont Zanclea sp. - Simone Montano; Davide Seveso; Paolo Galli; Stefania Puce; Bert W. Hoeksema (Marine Biology Research, 2015)

First record of coral-associated Zanclea (Hydrozoa, Zancleidae) from the Red Sea - Simone Montano; Paolo Galli; Davide Maggioni; Davide Seveso; Stefania Puce (Marine Biodiversity, 2014)

A phylogeny reconstruction of the Dendrophylliidae (Cnidaria, Scleractinia) based on molecular and micromorphological criteria, and its ecological implications - Roberto Arrigoni; Yuko F. Kitano; Jaroslaw Stolarski; Bert W. Hoeksema; Hironobu Fukami; Fabrizio Stefani; Paolo Galli; Simone Montano; Elisa Castoldi; Francesca Benzoni (Zoologica Scripta, 2014)
Recent molecular phylogenetic studies have shown that most traditional families of zooxanthellate shallow‐water scleractinians are polyphyletic, whereas most families mainly composed of deep‐sea and azooxanthellate species are monophyletic. In this context, the family Dendrophylliidae (Cnidaria, Scleractinia) has unique features. It shows a remarkable variation of morphological and ecological traits by including species that are either colonial or solitary, zooxanthellate or azooxanthellate, and inhabiting shallow or deep water. Despite this morphological heterogeneity, recent molecular works have confirmed that this family is monophyletic. Nevertheless, what so far is known about the evolutionary relationships within this family, is predominantly based on skeleton macromorphology, while most of its species have remained unstudied from a molecular point of view. Therefore, we analysed 11 dendrophylliid genera, four of which were investigated for the first time, and 30 species at molecular, micromorphological and microstructural levels. We present a robust molecular phylogeny reconstruction based on two mitochondrial markers ( COI and the intergenic spacer between COI and 16S) and one nuclear ( rDNA ), which is used as basis to compare micromorphogical and microstructural character states within the family. The monophyly of the Dendrophylliidae is well supported by molecular data and also by the presence of rapid accretion deposits, which are ca . 5 μ m in diameter and arranged in irregular clusters, and fibres that thicken the skeleton organized in small patches of a few micrometres in diameter. However, all genera represented by at least two species are not monophyletic, Tubastraea excluded. They were defined by traditional macromorphological characters that appear affected by convergence, homoplasy and intraspecific variation. Micromorphogical and microstructural analyses do not support the distinction of clades, with the exception of the organization of thickening deposits for the Tubastraea clade.

Assessing coral bleaching and recovery with a colour reference card in Watamu Marine Park, Kenya - Simone Montano; Davide Seveso; Paolo Galli; David O. Obura (Hydrobiologia, 2010)